1997
DOI: 10.1002/elps.1150181413
|View full text |Cite
|
Sign up to set email alerts
|

Preparative two‐dimensional gel electrophoresis of membrane proteins

Abstract: Electrophoretic techniques, and especially two-dimensional gel electrophoresis (2-DE), have provided an indispensable set of tools for the separation of complex protein mixtures as well as for the identification of protein-protein interactions. Nevertheless, after its introduction more than twenty years ago and even with recent technical developments, the separation of integral and peripheral membrane proteins, in amounts sufficient for microsequencing, is still a difficult task. Lipids present in the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 34 publications
3
123
0
Order By: Relevance
“…Silver nitrate staining according to the protocol of Pasquai et al (16) and Coomassie Brilliant Blue R-250 (0.25% Brilliant Blue, 10% v/v acetic acid, 50% v/v methanol, destained in 20% v/v EtOH, 10% v/v acetic acid) was used for the analytical and micropreparative gels, respectively. The two-dimensional electrophoresisl images were captured with a ImageScanner (Amersham Pharmacia Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…Silver nitrate staining according to the protocol of Pasquai et al (16) and Coomassie Brilliant Blue R-250 (0.25% Brilliant Blue, 10% v/v acetic acid, 50% v/v methanol, destained in 20% v/v EtOH, 10% v/v acetic acid) was used for the analytical and micropreparative gels, respectively. The two-dimensional electrophoresisl images were captured with a ImageScanner (Amersham Pharmacia Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…Two-dimensional gel electrophoresis was performed with non-linear immobilized pH gradient strips, pH range 3-10 (Amersham Pharmacia Biotech, Uppsala, Sweden) as described (36,37).…”
Section: Methodsmentioning
confidence: 99%
“…We followed methods recently described by Rabilloud et al (26) and Pasquali et al (22), which show that the inclusion of thiourea in the extraction buffer significantly expands the range of integral membrane proteins that can be analyzed by 2D PAGE. Our preliminary work confirmed that thiourea dramatically increased the number of spots visible on 2D gels of PM preparations (data not shown).…”
Section: Analysis Of Pm Proteomesmentioning
confidence: 99%